Morfodinâmica e meio ambiente na porção centro-norte do Piauí, Brasil - Iracilde Maria de Moura Fe Lima (2013)
The geomorphological studies on the Piauí space are at the initial stage of development. To contribute to the understanding of the dynamics of relief and its environmental landscapes in the state, the average area formed by the interfluve Parnaíba and down Poti were chosen as an object of study. With 6,380 km², it corresponds to a topographic compartment/ geological/hydrological that stands out in the Hydrographic Parnaíba basin as a space that is individualized from its surroundings by presenting environmental dynamic. This dynamic reflects in the spatial configuration of a large "island" that circumvented by regional rivers: the Parnaíba, the Poti and its tributaries, the Mulato and the Berlengas, has in its central portion the common topographic divider to the local drainage. From the reading of geological maps, topographic, hydrographic and SRTM and Landsat images, we sought evidence that the geological control of the dominant forms of local relief similar to what occurs in the regional modeled. This observation led to the hypothesis that would have been a remodeling from the Parnaíba river embedding and performance of morphogenetic processes resulting from this which are newer to the detriment of litho-structural control organized by the end of the Mesozoic. The overall goal is to understand the morphodynamic relief center-north of Piauí and its relations with other biophysical components of the environment, especially the dynamics of drainage of the Parnaíba River and its participation in the evolution of the environments of the sets of sub-the average Parnaíba basins and low Poti. The specifics objectives: 1) identify the geological conditions for the recent geomorphological dynamics, from the analysis of the right bank of the mid Parnaíba; 2) generate thematic maps and topographic-geological charts of the natural environment to support the analysis and synthesis as the dynamics of the areas of the main drainage of the area; 3) to map and characterize the relief of units resulting from the current morphodynamics, using as a basic reference the Relief Roughness Index (ICR); 4) identify the local river system dissecting processes, from the drainage of the dynamics driven by the Parnaíba river and its current position in relation to the topography, and the stratigraphic column of the Sedimentary Basin Parnaíba; 5) contribute to the study of the natural environment of the area, and the physical and chemical composition of the local drainage waters. As analytical basis, we used the integrated vision of general systems theory, especially that guides CSIRO work on integrated assessment studies of natural resources such as support for the proposed mapping of geomorphological units, with the conductor axis recent morphodynamic local landscapes. The analysis was conducted from the organization and interpretation of thematic maps of the study area, based on the understanding that the maps are not only a synthesis, but also a tool for geomorphological analysis at various stages of development of a geomorphological research. The analytical research framework is based on the premise that the recent dynamics of the study area landscape must lie predominantly expressed by the degree of dissection of relief and accumulation of sediment producing modeled locations, liabilities can be observed and identified in the landscape and their materials. The variables used to characterize the recent dynamics of relief, from the relations established between relief and other components of the natural environment in each set of sub-basins were mainly litho-structural elements, the current climate, slope of slopes, relief roughness classes, flow, longitudinal profile of rivers, the physical and chemical composition of the water, X-ray diffraction of soil clays, as well as the relative participation of elements of the natural environment. The structure of the work was organized in three sets: the first delimitation of the study area, based on the analysis ofgeological and hydrographic mapping, and the Landsat TM images and SRTM. These data bases were worked in ArcGIS and Global Mapper programs. The second set corresponded to the organization/preparation of thematic maps, illustrations and systematization of data on the rivers of the sub-basins sets Parnaíba and Poti, followed by the mapping and characterization of the units and subunits of relief that area, from the calculation and spatial of roughness Relief Concentration Ratios (ICR), and the development of DEMs from various locations of the whole study area, with the support of field work. For the definition of areas of plains and river terraces were used Google Earth images and technical information of wells drilled on the right bank of the Parnaíba River in the city of Teresina, linking them to field observations. In the third, a comparative analysis of the dynamics of the areas formed by the sub-basins sets, as a way to check the role of each factor in the dynamics of relief was performeds. Given the results achieved, it was considered partially accepts the hypothesis at the outset, as a part of the study area, the sub-basin of the stream San Francisco, located in the area of Graben of Mesozoic in Agricolândia, remains heavily dependent the litho-structural control; while the sub-basins of the river Poti and Parnaíba river present restructuring of the dynamic surface, setting a new standard of landforms. This results from the recent and growing influence of the incision of the Parnaíba River drainage system, expanding the membership of relief with the drain and its effects on the slopes and reducing the direct influence of geological structure. It was identified that the Parnaíba River drainage system in the embedding process of its valley created altimetry gaps that reach 350 meters between your bed and the top of the main topographical divisor of its tributaries, saw the Grajaú. Your position in the stratigraphic column of the Sedimentary Basin Parnaíba brought out on the slopes the sequence of rocks that make up the Geological formations from the Carboniferous to Jurassic, showing therefore the great intensity of Morphogenesis Cenozoic expressed processes, especially in hydrological capacity of that river. It was felt also that it can be inferred as to the contemporary carving the river Poti process to form your big mouth on the eastern edge of the Sedimentary Basin Parnaíba. The results indicate, therefore, a morphodynamic directed, in part, by the river Parnaíba, demonstrating its enormous influence and importance in the geomorphological and geo-environmental evolution also in the aspects of use and occupation of land of the study area.